Epidemiology of Indigenous Dengue Cases in Zhejiang Province, Southeast China - Ren, Jiangping; Chen, Zhiping; Ling, Feng; Huang, Yangmei; Gong, Zhenyu; Liu, Ying; Mao, Zhiyuan; Lin, Chunping; Yan, Hao; Shi, Xuguang; Zhang, Rong; Guo, Song; et al. (Frontiers in Public Health, 2022)
Objective: Dengue is one of the most widely distributed mosquito-borne diseases. In recent years, dengue outbreak occurred frequently in Zhejiang Province which prompted us to summarize the characteristics of these outbreaks for further control and prevention. Methods: Descriptive and spatiotemporal cluster analyses were conducted to characterize the epidemiology of autochthonous Dengue virus (DENV) transmission. Molecular epidemiology was used to identify the source of infection. Results: Totally, 1654 indigenous cases and 12 outbreaks, with no death, were reported during 2004-2018. Before 2017, all outbreaks occurred in suburban areas. During 2017-2018, 5 out of 8 outbreaks happened in urban areas. Of note, the median duration of outbreaks (28 days) in 2017-2018 was significantly shortened (P=0.028), by comparison to that in 2004-2016 (71 days). The median onset-visiting time, visiting-confirmation time and onset-confirmation time was 1 day, 3 days and 4 days, respectively. The DENV serotypes responsible for the autochthonous transmission in Zhejiang were type 1, type 2, and type 3, with serotype 1 as the most frequently reported one. Southeast Asia was the predominant source of infection. Conclusions: Zhejiang Province witnessed the increase in the frequency, incidence and geographic expansion of indigenous dengue cases in the past years. The more developed coastal and central region of the province is disproportionately impacted.